Synthesis, Evaluation Antimicrobial Activity of Some New N-substituted Naphthalimides Containing Different Heterocyclic Rings - Ahmad, Mohammed; Al-Majidi, Suaad; Khan, Ayad (Iraqi Journal of Science, 2024)
A series of new 1,8-naphthalimides linked to azetidinone, thiazolidinone or tetrazole moieties were synthesized. N-ester-1,8-naphthalimide (1) was obtained by direct imidation of 1,8-naphthalic anhydride with ethylglycinate. Compound (1) was treated with hydrazine hydrate in absolute ethanol to give N-acetohydrazide-1,8-naphthalimide (2). The hydrazine derivative (2) was used to obtain new Schiff bases (3-7). Three routes with different reagents were used for the cyclization of the prepared Schiff bases. Fifteen cyclic Schiff bases (8-22) with four- and five-membered rings were obtained.The structures of the newly synthesized compounds were identified by their FTIR, 1H-NMR, 13C-NMR spectral data and some physical properties. Furthermore, these compounds were screened in three concentration for their in vitro antimicrobial activity measurements against both Gram (+ve) such as Staphylococcus aureus, Bacillus and Gram (-ve) Escherichia Coli, pseudomonas aeuroginosa bacteria and against Candida albicans fungal and they were found to exhibit good to moderate antimicrobial activities.